IMPLEMENTASI PEMBELAJARAN BERBICARA MENGGUNAKAN METODE LIHAT UCAP PADA SISWA KELAS I DI SDN 014 UJUNG TANJUNG - Nurmilian, Nurmilian (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
Speaking, in essence, is a process of communicating, because messages occur from one source to another. The purpose of this study is to describe the implementation of speaking learning using the method of seeing. This research is a classroom action research with 12 research subjects in Ujung Tanjung SDN 014 Benai Subdistrict Kuantan Singingi Regency with the results of research on improving students' speaking skills from the initial data to the first cycle is 30.09%, from the base score of 49, 47 increased to 64.36 in the daily cycle I cycle, while the initial data for the second cycle increased by 60.56%, from the average score of 49.47 to 79.43. Based on the results of the study it can be concluded that the method of seeing said is effectively used in learning to speak.